2005
DOI: 10.1203/01.pdr.0000155948.83570.eb
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term (0–48 h) Effects of Maternal Betamethasone Administration on Fetal Heart Rate and Its Variability

Abstract: The short-term (0 -48 h) effects of maternal betamethasone administration on computerized fetal heart rate (FHR) parameters were studied in 36 pregnancies at increased risk for preterm delivery. FHR was recorded for 90 min immediately before the start of betamethasone treatment and again at 6-h intervals during the next 48 h. Multiple linear regression models were used to assess the possible effects on FHR parameters of gestational age, time of day, clinical indication for treatment, and use of tocolytic drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
3
12
1
Order By: Relevance
“…Greater exposure to maternal cortisol during gestation may reduce infant ability to develop the physiological reserve capacity that is needed to regulate responses to physical and social environments; and this reduced capacity may help to explain the association between lower basal CVC and reduced socio-emotional competence (Liew et al, 2011) and effortful control of attention (Taylor et al, 2015) in children with elevated cortisol exposure. These results are also consistent with previous reports of an inverse association between exposure to synthetic glucocorticoids in utero and fetal basal CVC (Lunshof et al, 2005;Schneider et al, 2010;Senat et al, 1998). Our findings suggest that the effects of exogenous glucocorticoids on fetal CVC are similar to the effects of endogenous maternal cortisol on infant CVC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Greater exposure to maternal cortisol during gestation may reduce infant ability to develop the physiological reserve capacity that is needed to regulate responses to physical and social environments; and this reduced capacity may help to explain the association between lower basal CVC and reduced socio-emotional competence (Liew et al, 2011) and effortful control of attention (Taylor et al, 2015) in children with elevated cortisol exposure. These results are also consistent with previous reports of an inverse association between exposure to synthetic glucocorticoids in utero and fetal basal CVC (Lunshof et al, 2005;Schneider et al, 2010;Senat et al, 1998). Our findings suggest that the effects of exogenous glucocorticoids on fetal CVC are similar to the effects of endogenous maternal cortisol on infant CVC.…”
Section: Discussionsupporting
confidence: 93%
“…Fetal CVC was reduced following the administration of betamethasone delivered during the third trimester to 8 pregnant mothers at risk of preterm labor (Schneider et al, 2010). Further, shortterm variability in fetal HR increased transiently after the administration of betamethasone followed by a significant reduction that spanned 2-7 days (Lunshof et al, 2005;Senat et al, 1998). In addition, cortical thinning was observed in children between 6 and 10 years of age who were exposed to synthetic glucocorticoids during fetal development (Davis et al, 2013).…”
Section: Cortisol During Pregnancy and Cardiac Vagal Controlmentioning
confidence: 99%
“…In animal models, it did not affect the maternal heart rate and blood pressure increased fetal blood pressure (23). It had mild effect on the fetal heart rate (24). Although in some investigations, it was found that it did not affect Doppler parameters of UA, UtA, and MCA, in some, a decrease in Doppler indices of UA and MCA (25,26) and ductus venosus, particularly PI of MCA, was seen (27).…”
Section: Discussionmentioning
confidence: 96%
“…However, this effect was relatively small, with a 3% to 5% decrease in mfHR. 21,27 On days 2 and 3, a trend was seen toward an increase in mfHR in multiple studies. 20,24,27 This trend was significant only in fetuses younger than 27.5 weeks' GA. 25 Other studies showed no effect on mfHR after corticosteroid administration during the study period.…”
Section: Betamethasonementioning
confidence: 95%